Mobility of electrons and holes in a liquid crystalline perylene diimide thin film with time of flight technique - Kim, JY; Chung, IJ; Kim, YC; Yu, JW (ELSEVIER SCIENCE BV, 2004)
When NN'-diheptyl-3,4,9,10-perylenebiscarboximide (PTCDI-C7) was evaporated on an ITO glass substrate, a vapor-deposited polycrystalline film was normally obtained. It was then thermally treated on its liquid crystalline phase to get an ordered intermolecular structure. Then an ITO/PTCDI-C7/A1 device was fabricated to study the drift mobility of electrons and holes by means of time-of-flight techniques. The negative charges were measured faster than the positive ones, as expected for an n-type organic semiconductor: the electron and the hole mobilities were 0.0139 and 0.0089 cm(2)/(Vs), respectively, at an electric field of 186 (V/cm)(1/2). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: TRANSPORT; PHTHALOCYANINE; TRANSISTOR